Corrosion of Ti3AlC2 at 800-1100 degrees C in Ar-0.2% SO2 gas atmosphere - Lee, Dong Bok; Park, Sang Whan (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
Ti3AlC2 was corroded between 800 and 1100 degrees C in an Ar-0.2% SO2 gas atmosphere according to the equation: Ti3AlC2 + O-2 --> rutile-TiO2 + alpha-Al2O3 + (CO or CO2). The scales that formed on the Ti3AlC2 were thin and rich in alpha-Al2O3, whose growth rate was exceedingly slow. The TiO2 was present either as the outermost surface scale or a mixture inside the alpha-Al2O3-rich scale. In the Ti3AlC2, the activity and diffusivity of Ti were low, whereas those of Al were high. This was the main reason for the superior corrosion resistance of Ti3AlC2 over TiAl. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: HIGH-TEMPERATURE CORROSION; OXIDATION BEHAVIOR; TIN+1ALXN N=1-3; AIR; CERAMICS; ALLOYS; TI2ALC; TI